Efisiensi Program Dana Pensiun Lembaga Keuangan Muamalat dalam Mengelola Dana Pensiun Syariah di Kabupaten Cirebon - Nurul Alifiya; Ika Fijriya; Anwar Ihsan Hidayat; Fahmi Sabila Nugraha (STIKes Ibnu Sina Ajibarang, 2025)
Often, the quality of human life, whether individually, in groups, communities, or countries, becomes a benchmark for economic welfare. The purpose of this study is to determine the effectiveness of the DPLK Syariah Muamalat program in Cirebon Regency. In this study, a descriptive qualitative approach is used. This is to describe and explain certain phenomena, conditions, or events in the existing data. The results of the study show that DPLK Muamalat as a sharia-based pension fund management institution has high efficiency by investing in halal instruments such as sukuk, sharia stocks, and sharia deposits. The programs offered include individual and corporate pension funds with investment flexibility, management transparency, and digital-based services. The marketing strategy is focused on education and collaboration to increase public literacy about the importance of sharia pension funds. Despite facing the challenge of low public understanding, DPLK Muamalat has a great opportunity as the only sharia-based DPLK in Indonesia.